Synthesis and Antiproliferative Activity of Quinolone Nucleosides Against the Human Myelogenous Leukemia K‐562 Cell Line. Issue 10 (16th September 2013) - Wicke, Lena; Engels, Joachim W.; Gambari, Roberto; Saab, Antoine M.
<x xml:space="preserve">Abstract</x> A set of 6‐substituted quinolone nucleosides linked to aniline or phenol via N or O heteroatom‐bridges presenting new compounds were synthesized by palladium‐catalyzed Buchwald–Hartwig cross‐coupling reactions. 6‐Bromoquinolone nucleoside precursors, being protected by either benzoyl or TBDMS protecting groups on the ribose moiety, were subjected to different Buchwald–Hartwig conditions as the key step. Defined deprotection steps led, in good yields, to the final target compounds that carry, in position 3, either ester, acid, or amide functions. Thus, a series of novel quinolone nucleoside derivatives was obtained via a convergent synthesis route. Biological tests in human chronic myelogenous leukemia K562 cells exerted an efficient antiproliferative activity for two of them without induction of differentiation. These novel nucleosides deserve further experiments to determine their antiproliferative effects on other CML cell lines.